Do they do as they say? Analysing the impact of Brexit on relocation intentions in the UK's FinTech industry - Franziska Sohns; Dariusz Wójcik (ZFW - Advances in Economic Geography, 2023)
This paper responds to Bathelt and Li's (2020) call for selecting more appropriate methods and improving their rigour by evaluating the feasibility of using factorial surveys to anticipate future relocation behaviour. By utilising a case study approach, focussing on Brexit and the UK FinTech industry, the paper examines to what extent business managers' relocation intentions are driven by factors similar to those known to drive actual relocation behaviour and compares business managers' relocation intentions with their companies' actual relocation outcomes. We use a factorial survey conducted in 2018, which allows us to quantitatively analyse the impact of different Brexit scenarios and selected company characteristics on business managers' likelihood to intend to relocate their UK business unit (or some functions thereof) to the EU and/or the US. Additionally, we collected qualitative secondary data on the actual relocation outcomes of the surveyed companies in February 2022 by investigating online platforms, such as LinkedIn, Companies House, and Crunchbase, as well as company webpages. The results of this mixed-methods approach highlight a significant variation in business managers' intentions, and the importance of geographical and institutional proximity for relocation intentions and outcomes. We show that business managers' relocation intentions are driven by factors similar to those known to drive actual relocation behaviour, such as their perception of the economic consequences of different Brexit scenarios, their territorial embeddedness, as well as their nationality. Most importantly, our findings indicate that, although factorial surveys are only moderately accurate when predicting the exact extent and destination of actual relocation, they are highly accurate when predicting whether a company relocates or not.
Keywords: 330; Brexit; financial services; international financial centres; Paris; London